Efektivitas Pengendalian Risiko atas Penjualan Jasa Makeup di Cv. Arester Nugraha - Lutfah, Risma Ismayanti; Saepulo, Cepi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to evaluate the effectiveness of risk control for the sale of makeup services at CV Arester Nugraha, specifically in addressing the practice of secret selling carried out by some makeup artists (MUAs). The research method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that although the company has established risk control procedures and policies in the form of SOPs and a sales recording system, implementation in the field is not optimal. This is evident in the ongoing practice of selling services privately by MUAs without going through official company channels. The main obstacles to the effectiveness of risk control include weak supervision, unclear sanctions, and a lack of satisfaction with the commission sharing system. Efforts that have been made by the company to overcome these obstacles include re-socializing internal policies, strengthening communication between teams, and enforcing disciplinary sanctions. The conclusion of this study is that the implemented risk control is still not fully effective and requires improvements in aspects of implementation and continuous monitoring.